P-37 The economic impact of a clinical nurse specialist (CNS) triage role within a community specialist palliative care service. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Gibson, Vanessa; Kavanagh, Maria; Patel, June
Abstract : Within a community based specialist palliative care service the introduction of a CNS triage post has provided many practical benefits, not least: triage of referrals, assessment of urgency, co-ordination of services provision of immediate specialist advice to patients, families and professionals increased support to the CNS team ensuring referrals are appropriate, want contact and all necessary supporting clinical information is in place, facilitating timely and comprehensive patient contact. A key benefit for St Richard's Hospice however has been a significant reduction in the number of unnecessary home visits. We are able to demonstrate that in the following instances unnecessary home visits can be prevented: New referrals to the service who may be inappropriate or chose not to access services available Prior to discharge the patient can be offered 'step down' telephone contact Use of telephone caseload to provide regular contact for patients who do not want a CNS home visit Use of an increasingly busy helpline facility which supports patients self-management and crisis prevention As part of a Royal College of Nursing and Office of Public Management initiative to develop nurses economic assessment skills the community nursing services manager has been able to apply an economic value in the terms of cost savings produced by the successful introduction and ongoing refinement of the triage role. These cost savings will be explored in conjunction with identified patient benefits which include: Increased choice- the level of service provided is tailored to patient needs and preferences Increased flexibility and time to spend with the most complex patients as CNS capacity has been released Supported discharge, reducing anxiety and promoting self-management Accessible immediate specialist advice for patients and families providing ongoing reassurance, reducing the risk of crisis and unnecessary admissions Confidence in a co-ordinated team approach rather than over dependence on one team member We have an effective and transferable model in place providing multiple benefits for patients, CNS team and the organisation.